Stock returns and implied volatility: A new VAR approach - Bong Soo Lee; Doojin Ryu (Kiel Institute for the World Economy (IfW), 2012)
This study re-examines the return-volatility relationship and dynamics under a new VAR framework. By analyzing two model-free implied volatility indices - VIX (the U.S.) and VKOSPI (Korea) - and their corresponding stock market indices, we found an asymmetric volatility phenomenon in both developed and emerging markets. However, the VKOSPI, a recently published implied volatility index, shows impulse response dynamics that are clearly distinct from those for the VIX, an implied volatility index for the developed market.
Keywords: G10; G15; 330; asymmetric volatility; vector autoregression; VIX; VKOSPI